Analisis Pertumbuhan Ekonomi dan Ketimpangan Wilayah Sebagai Dampak Pembangunan Infrastruktur Pertanian di Kabupaten Belu - Taena, Werenfridus; Sipayung, Boanerges Putra; Blegur, Fried Markus Allung; Klau, Anggelina Delviana (Fakultas Pertanian, Universitas Timor, 2024)
The research objectives are to analyze (1) the level of regional development based on infrastructure availability, (2) regional economic growth, (3) regional inequality (4) the relationship between economic growth and regional inequality in Belu Regency. The data used is GRDP data per sub-district in Belu Regency from 2016 to 2020. Data analysis uses scalograms, economic growth, Williamson index, and correlation. The results of the analysis state that the development of agricultural infrastructure in Kakuluk Mesak District has contributed to the development of the Kakuluk Mesak sub-district area so that it occupies hierarchy II. The impact is an increase in economic growth and regional inequality. Kakuluk Mesak District, which is the location where the Rotiklot Dam was built, has a high correlation between economic growth and regional inequality. Therefore, it is recommended that infrastructure development be more balanced between regions so that equitable development can be achieved.